Effects of Eucalyptus (Melaleuca cajuputica) and Patchouli (Pogostemon cablin) Essential Oils on Mortality of Mealybugs (Planococcus minor) on Mangosteen - Syaf, Mia Sri Lestari; Dewi, Vira Kusuma; Puspasari, Lindung Tri; Ismayati, Maya (CROPSAVER, 2024)
Planococcus minor is one of the pests prohibited from entering several destination countries during the mangosteen export process. Control of P. minor can be achieved by using patchouli and eucalyptus essential oils. The objective of this research is to determine the effects of patchouli and eucalyptus essential oils on the mortality of P. minor, with the aim of developing control measures to prevent mangosteen export failures. This study was conducted at the Class 1 Agricultural Quarantine Station in Bandung from May to December 2023. The method used is the experimental method with a Randomized Complete Block Design. Contact and neurophysiological tests were conducted with 13 treatments, including distilled water control, distilled water + tween 80 control, synthetic pesticide with abamectin 0.005%, patchouli essential oil at concentrations of 0.13%, 0.18%, 0.24%, 0.32%, 0.43%, and eucalyptus essential oil at concentrations of 0.22%, 0.29%, 0.39%, 0.51%, 0.68%, each repeated three times. The research results indicate that mortality of P. minor caused by 0.43% concentration of patchouli essential oil did not significantly differ from abamectin, with a rate of 96.67%. The LC50 values for patchouli and eucalyptus essential oils were 0.19% and 0.42%, respectively. The LT50 value of eucalyptus essential oil is lower when compared to the LT50 value of patchouli essential oil. The LT50 value of eucalyptus essential oil at the highest concentration of 0.68% was 49.94 JSP. Patchouli essential oil at concentrations of 0.43% and 0.32% had different LT50 values of 37.27 and 50.73 JSP. Furthermore, based on morphological observations that eucalyptus and patchouli essential oils affect the morphology of mealybugs.